The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1038/srep36059
|View full text |Cite
|
Sign up to set email alerts
|

Temperature- and wavelength-insensitive parametric amplification enabled by noncollinear achromatic phase-matching

Abstract: Optical parametric chirped-pulse amplification (OPCPA) has been demonstrated to be a promising approach for pushing femtosecond pulses towards ultra-high peak powers. However, the future success of OPCPA strongly relies on the ability to manipulate its phase-matching (PM) configuration. When a high average power pump laser is involved, the thermal effects in nonlinear crystals induce phase-mismatch distortions that pose an inherent limitation on the conversion efficiency. Here, we demonstrate that the noncolli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 38 publications
(41 reference statements)
0
8
0
Order By: Relevance
“…The non-collinear OPCPA configuration was previously devoted to achieving wavelength-insensitive phase-matching with a large spectral bandwidth (Figure 35(b)). Notably, it was recently found that the non-collinear phase-matching configuration can also make OPCPA insensitive to temperature by setting an appropriate non-collinear angle [255] . In an LBO-crystal-based OPCPA with and , the non-collinear phase-matching can be designed for either with or with .…”
Section: Future Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-collinear OPCPA configuration was previously devoted to achieving wavelength-insensitive phase-matching with a large spectral bandwidth (Figure 35(b)). Notably, it was recently found that the non-collinear phase-matching configuration can also make OPCPA insensitive to temperature by setting an appropriate non-collinear angle [255] . In an LBO-crystal-based OPCPA with and , the non-collinear phase-matching can be designed for either with or with .…”
Section: Future Technologiesmentioning
confidence: 99%
“…In an LBO-crystal-based OPCPA with and , the two non-collinear angles for and are equal to each other at the crystal reference temperature of 337 K. As a result, the spectral bandwidth of such an OPCPA phase-matching design was similar to that in conventional wavelength-insensitive non-collinear phase-matching, while the temperature acceptance was increased by a factor of 4.3. Due to its ability to simultaneously support broadband amplification and large temperature bandwidth, the temperature-insensitive OPCPA design may provide a promising way to generate ultra-intense lasers with kW average powers [255, 256] .…”
Section: Future Technologiesmentioning
confidence: 99%
“…On the other hand, the noncollinear angle ρ s between the signal and pump can be utilized for temperature-insensitive PM ( k/T = 0, but k/λࣔ0). Such a temperature-insensitive nonlinear PM configuration has been applied to OPCPA, resulting in a five-fold enhancement in the temperature acceptance [37]. In the QPCPA process with a 532-nm pump and an 800-nm seed, either k/T = 0 or k/λ = 0 can be achieved by setting the noncollinear PM angle to ρ s = 6.12 • or ρ s = 2.68 • in the XY plane of the Sm:YCOB crystal, respectively.…”
Section: Qpcpa With Temperature-insensitive Noncollinear Pmmentioning
confidence: 99%
“…In the QPCPA process with a 532-nm pump and an 800-nm seed, either k/T = 0 or k/λ = 0 can be achieved by setting the noncollinear PM angle to ρ s = 6.12 • or ρ s = 2.68 • in the XY plane of the Sm:YCOB crystal, respectively. As these two noncollinear angles are not equal, angular dispersion of the seed signal must be introduced to ensure broadband PM if we set ρ s to 6.12°f or k/T = 0, as in [37]. The required angular dispersion for the signal is approximately 104 μrad/nm, which can be produced or compensated by slightly misaligning the pulse stretcher or compressor.…”
Section: Qpcpa With Temperature-insensitive Noncollinear Pmmentioning
confidence: 99%
“…In case of the central frequencies, the magnitude of k 0i is equal to the real magnitude of the idler wave vector k 0i , which can be obtained from the dispersion relation in Eq 2. 96. However, for general signal and idler frequency pairs the magnitude of k i and k i is not necessarily equal.…”
Section: Broadband Phase-matching Geometrymentioning
confidence: 99%